A cobertura florestal da paisagem afeta negativamente a remoção de diásporos por formigas - Alves, Guilherme Pereira (2019)
Humans have modified terrestrial ecosystems through activities that cause natural habitat loss, and consequently the reduction of terrestrial biodiversity (e.g. simplification of communities and loss of ecological services and functions). In recent decades the pace of anthropogenic fragmentation has become more rapid, especially as agricultural areas, logging and urban development have increased. In this study we focus specifically on the removal of diaspores by ants, an extremely important ecological function, as it can increase the chances of seed germination, affect plant survival, abundance and distribution. In this context, our aim was to understand how the removal of diaspores by ants is affected by the loss of landscape forest cover. The study was conducted in 30 landscapes with different levels of forest cover of the Atlantic Forest biome, in Minas Gerais state, Brazil. In each sampled landscape, we placed four sample points 20 meters apart from each other in a fragment in the center of the landscape. We provided 100 artificial diaspores at each of the sampling points for 24 hours, and then counted how many diaspores were removed. We used Generalized Linear Models to test whether the percentage of forest cover in a landscape affects the removal of diaspores. We found that the percentage of forest cover in the landscape correlates negatively with seed removal. Land use change in landscapes with less forest cover may also have modified species composition, so more species could possibly perform the role of seed remover. Our results strengthen our knowledge of the importance of ants in relation to diaspore removal in landscapes with less forest cover, because they could initiate recovery of this more degraded environment.